2018
DOI: 10.1371/journal.pone.0203998
|View full text |Cite
|
Sign up to set email alerts
|

Workplace psychosocial stressors experienced by migrant workers in Australia: A cross-sectional study

Abstract: ObjectiveTo explore work-related psychosocial stressors among people of Chinese, Vietnamese and Arabic-speaking backgrounds currently working in Australia.MethodsIn 2015, a telephone survey of 585 Vietnamese, Chinese and Arabic-speaking workers asked about workplace bullying, ethnic discrimination, job complexity, degree of control, security and fairness of payment along with demographic and employment information. Estimates of job-related psychosocial stressors were derived and regression analyses used to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…9 In addition, psychological stressors, such as perceived job insecurity, or a lower job satisfaction, do have an impact on the mental well-being of the migrant workers. 10 A hospital-based study was conducted in Malaysia in 1998 to identify the prevalence of psychiatric disorders among the patients from the Association of Southeast Asian Nations (ASEAN) migrants. The study found that the majority of migrant patients admitted to the psychiatric ward were unskilled workers (76.9%; n = 39).…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, psychological stressors, such as perceived job insecurity, or a lower job satisfaction, do have an impact on the mental well-being of the migrant workers. 10 A hospital-based study was conducted in Malaysia in 1998 to identify the prevalence of psychiatric disorders among the patients from the Association of Southeast Asian Nations (ASEAN) migrants. The study found that the majority of migrant patients admitted to the psychiatric ward were unskilled workers (76.9%; n = 39).…”
Section: Introductionmentioning
confidence: 99%
“…From our results, migrant workers with high school or lower educational attainment had similar job insecurity to Australia-born workers 5+ years post-arrival, which may be partly because lower educated workers may have a lower risk of status inconsistency. Moreover, discrimination may also play a role in higher job insecurity among overeducated migrants, because job insecurity combined with ethnic discrimination has been reported to be the most common combination of psychosocial job stressors among Australian migrant workers [34]. Ethnic and racial minority groups, including migrants, have been reported to be targets of discrimination-related job loss [54], resulting in migrants being the ‘last hired’ and ‘first fired’ [55].…”
Section: Discussionmentioning
confidence: 99%
“…The number of migrants in Australia is increasing, and nearly 60% are employed [32]. Despite job insecurity being reportedly common among migrant workers [28,33,34], there are few studies on migrants’ job insecurity in Australia [34,35,36,37]. Among those, Daly, Carey, Darcey, Chih, LaMontagne, Milner, and Reid [37] reported that Australia-born workers had lower job insecurity than migrant workers, and McGuinness and Wooden [35] reported that migrants from non-English speaking countries (non-ESC-born) and recently arrived migrants had higher levels of job insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that targets of incivility tended to demotivate wellbeing, job satisfaction, work effort, and a higher work turnover (Loh & Loi 2018). Moreover, when employees frequently faced such noxious aspects of the work environment, they become less motivated and unable to focus on their job (Daly & Carey, 2018). In the line of hectic restaurant environment, factors such as rude customers, co-workers or an angry supervisor, may be a fact of life for some employees (Olson & Sinsky, 2019).…”
Section: Introductionmentioning
confidence: 99%